COMPARING OF SOIL REFLECTANCE VALUES BY USING DIFFERENT PROGRAMS - Taha Abdul Hadi Taha Dawood Al-jawwadi (Mesopotamia Journal of Agriculture)
The Hatra area in Nineveh governorate / Iraq has been chosen for this research because it sits on in arid and semi arid area and because of the availability of its previous study with grounded digital imags, aerial photo and satellite images. We used a specialized tool in Photo Shop program by selecting a huge number may reach to thousands of pixels , and using the histogram window of the selecting area to know the average of RGB value, then calculating its reflections in mathematical formula, and comparing it with results of last studying used the same digital images but in few pixels. This study found that there is necessary to select a large number of pixels to digital image of rough surface of soil to read the reflectance because the clear difference with the previous study, but there is no clear different with lab preparing soft surface of soil.